Historical data analysis and future prediction of lung cancer in Zhejiang province, China - Yang Gao; Mengqi Zhang; Guangyuan Liu; Huiyue Lin; Hong Huang; Hongli Xie (Scientific Reports)
Abstract Environmental factors have known to cause lung cancer. However, the relationship between lung cancer and the environmental factors are not well explored or quantified. Using Zhejiang Province of China as a case study, the spatiotemporal distribution of lung cancer and associated environmental factors were investigated. The data of lung cancer were obtained from Zhejiang Cancer Registry Annual Report and China Cancer Registry Annual Report from 2000 to 2022. The environmental factors are derived from China County Statistical Yearbook and so on. The JoinPoint, SaTScan, spatial autocorrelation technologies and spatial regression models were used to investigate the spatiotemporal clustering, spatial distribution characteristics analysis and correlation of environmental factors of lung cancer. The incidences of lung cancer in Zhejiang Province increased over time, most incidences occurred in the north and became less so in the south of the province, showing a spatial aggregation distribution. The increase of urbanization rate has increased the incidence of lung cancer, and the proportion of environment-related lung adenocarcinoma has increased year by year. The spatial regression model showed that the incidence of lung cancer was negatively correlated with vegetation index, and positively correlated with annual average per capita GDP. There was spatial heterogeneity in the distribution of lung cancer incidence in Zhejiang Province, China, and the areas with high incidence were located in areas with high degree of industrialization and urbanization. Vegetation and urbanization rate have an impact on the incidence of lung cancer.